Combined Effect of Trichoderma viride with Other Phosphate Solubilizing Microorganisms on Soil Nutrient Availability and Uptake by Rice Plant - Donbiaksiam, Tabitha; Jyotsna, Nongmaithem (Scientific Research, New Technologies and Applications Vol. 4, 2024)
The present study highlights the combined effect of Trichoderma viride (T.V) with other Phosphate Solubilizing Microorganisms (PSM) on soil nutrient availability and uptake by Rice plants. T.V is widely used in the field of Soil science for its various contribution to agriculture. It makes soil nutrients available and therefore in this research, utilization of T.V is done along with other PSM to solubilize phosphorus(P). PSMs are ubiquitous, whose number varies from soil to soil and help in the mineralization of organic P in the soil. The present work was conducted under lower Gangetic alluvial at the Agricultural Experimental Station of Calcutta University, Baruipur, 24 Parganas (South), West Bengal in a Rice plant. The experiment was carried out with six treatments(T) replicated four times, T1@Trichoderma viride (T.V), T2@ Azotobacter chroococcum (A.C)+ Trichoderma viride (T.V), T3@ Pseudomonas striata (P.S) + Trichoderma viride (T.V), T4@Azotobacter chroococcum (A.C) + Pseudomonas striata (P.S)+ Trichoderma viride (T.V), T5@ Azotobacter chroococcum (A.C) and T6@Azotobacter chroococcum (A.C) + Pseudomonas striata (P.S). Out of the six treatments, T3 which received T.V and P.S showed the highest Carbon(c), P and Potassium(K) content and T6 showed the highest nitrogen(N) content in the soil. P availability is increased with the application of T.V and the combination of T.V with other PSM shows even higher solubilization of P in the soil.